A psychotherapy approach to treating hostile voices. Issue 2 (3rd April 2017) - Mosquera, Dolores; Ross, Colin
Abstract: Hostile voices are a common problem in both dissociative identity disorder and psychosis. They may take the form of command hallucinations for suicide, or express negative thoughts and feelings about the self. The authors describe a psychotherapeutic treatment approach for hostile voices that converse with each other, keep up a running commentary on the person's behavior, or otherwise speak in intelligible sentences and paragraphs. This approach can be useful, in the authors' opinion, whether the diagnosis is a psychotic or a dissociative disorder. The authors provide clinical detail, with a case example, on the psychotherapy of hostile voices.